Testing of the fire-proof functionality of cable insulation under fire conditions via insulation resistance measurements. (November 2015) - Polanský, R.; Polanská, M.
Abstract: Two different designs for low-fire-hazard cables were tested under conditions similar to those of the fire test specified in IEC 60331-21. In addition to the other standard requirements, an insulation resistance meter was connected directly to the measurement circuit to monitor the actual state of the cable insulation during the fire tests. The suitability of this measurement of the insulation resistance was demonstrated by testing cables with fire barriers made from mica glass tape and from ceramifiable silicone rubber. The results showed that insulation resistance is sensitively affected by the melting of the organic components of insulation, by the decomposition of the fire retardant, by the ignition of the core insulation and by the formation of a silica layer during a fire test. The results also helped to reveal the importance of flame conductivity in performing such tests. The initial observations are supported by thermogravimetry and differential scanning calorimetry, which are beneficial as a first step towards understanding the mechanisms of fire-proof functionality in cables. The suggested procedure can assist in the comparison of the fire-proof functionalities of different cable designs, in the analysis of their failure mechanisms and in cable design optimisation. Highlights: LFHC cable with a fire barrier made from mica tape is tested under fire conditions. Insulation resistance of the tested cables is monitored during fire tests. Resistance is affected by melting, decomposition and by ignition of the insulation. The initial observations are supported by TGA and DSC. Suggested test procedure can assist in the analysis of cable failure mechanisms.